FINANCIAL ACCOUNTING OF COMPANIES IN THE CONTEXT OF RELIABILITY - Мейш, Алла; Ядуха, Сергій (SWorldJournal, 2023)
The relevance of ensuring the reliability of accounting has been emphasized in the article. Attention has been drawn to the fact that, as a result of its alleged radical reformation, it is not possible to get rid of the imperfection of financial accountin